Psychology Services for Children Sex Abuse by The Technical Implementation Unit of Bandar Lampung City - Hana Rahadatul Aisy; Vania Ardelia (International Conference on Psychology and Education (ICPE), 2025)
Psychosocial services play a crucial role in supporting children who are victims of sexual abuse (CSA), particularly in areas with high case numbers such as Bandar Lampung. This paper discusses the psychological and social consequences of CSA on victims aged 4–17 years, emphasizing the prevalence of emotional disturbances such as anxiety, PTSD, and low self-esteem. Using qualitative methods through interviews and observations at the UPTD PPA Bandar Lampung, findings indicate that most victims come from lower economic backgrounds, with girls aged 6–12 being the most affected. The perpetrator-victim relationship is often close, involving neighbors, caregivers, or acquaintances. The discussion integrates theories such as attribution, bystander effect, conformity, sexism, and gender roles to understand community responses and systemic challenges. Additionally, the media’s role in desensitization and the need for comprehensive sex education are emphasized. Psychosocial services, especially those involving family, legal support, and therapeutic counseling, are essential for child recovery and community prevention efforts.